2017
DOI: 10.1080/1028415x.2017.1329976
|View full text |Cite
|
Sign up to set email alerts
|

Macular pigment optical density is positively associated with academic performance among preadolescent children

Abstract: This is the first study to demonstrate that retinal L and Z, measured as MPOD, is positively related to academic achievement in children, even after accounting for the robust effects of IQ and other demographic factors. These findings extend the positive associations observed between MPOD and cognitive abilities to a pediatric population. Trail registration: The Fitness Improves Thinking in Kids 2 (FITKids2) trial was registered at www.clinicaltrials.gov as NCT01619826.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 41 publications
1
31
0
1
Order By: Relevance
“…Macular pigment is widely believed to protect macular photoreceptors from short-wavelength blue light and oxidative damage (1,4). Recent research has increasingly implied that lutein and zeaxanthin play a role in cognitive function in adults (5)(6)(7)(8)(9), and more recently in children (10,11). Both infant and adult human brain contains lutein and zeaxanthin at higher levels than those observed for other carotenoids found in human plasma (8,12).…”
Section: Introductionmentioning
confidence: 99%
“…Macular pigment is widely believed to protect macular photoreceptors from short-wavelength blue light and oxidative damage (1,4). Recent research has increasingly implied that lutein and zeaxanthin play a role in cognitive function in adults (5)(6)(7)(8)(9), and more recently in children (10,11). Both infant and adult human brain contains lutein and zeaxanthin at higher levels than those observed for other carotenoids found in human plasma (8,12).…”
Section: Introductionmentioning
confidence: 99%
“…Given that the focus of the current work was on diet quality, it is difficult to isolate the particular nutrients that may confer the cognitive benefits. However, several of the food groups and nutrients that would be more prevalent in component 1 have been previously shown to positively impact cognitive health including saturated fatty acids (48), dietary fiber (17) and carotenoids from vegetables and other plant foods (49)(50)(51), and proteins and vitamin D to name only a few (52). Thus, future experimental work is needed to confirm whether consuming a diet pattern rich in these diet quality components would be beneficial for children's cognitive function in a prospective manner.…”
Section: Discussionmentioning
confidence: 99%
“…The brain, like the retina, actively accumulates xanthophylls, especially, L . A number of recent studies have shown that lutein status (i.e., measured in serum/diet and directly in retina, MP) correlates with a number of centrally‐mediated functions including numerous aspects of cognition . In addition, recent imaging studies also suggest a relationship between lutein and CNS functioning …”
Section: Introductionmentioning
confidence: 99%